Understanding Risks and Uncertainties in Energy and Climate Policy Multidisciplinary Methods and Tools for a Low Carbon Society - Doukas, Haris; Flamos, Alexandros; Lieu, Jenny (Springer Nature, 2019)
This open access book analyzes and seeks to consolidate the use of robust quantitative tools and qualitative methods for the design and assessment of energy and climate policies. In particular, it examines energy and climate policy performance and associated risks, as well as public acceptance and portfolio analysis in climate policy, and presents methods for evaluating the costs and benefits of flexible policy implementation as well as new framings for business and market actors. In turn, it discusses the development of alternative policy pathways and the identification of optimal switching points, drawing on concrete examples to do so. Lastly, it discusses climate change mitigation policies' implications for the agricultural, food, building, transportation, service and manufacturing sectors. ; Open Access Presents a comprehensive tool set of methods for devising energy and climate policies Focuses on methods that are robust and adaptive enough to mitigate risks Investigates implications of climate change mitigation policies to various sectors